Single-View Echocardiography by Nonexpert Practitioners to Detect Rheumatic Heart Disease: A Prospective Study of Diagnostic Accuracy. (August 2021) - Francis, Joshua R.; Whalley, Gillian A.; Kaethner, Alex; Fairhurst, Helen; Hardefeldt, Hilary; Reeves, Benjamin; Auld, Benjamin; Marangou, James; Horton, Ari; Wheaton, Gavin; Robertson, Terry; Ryan, Chelsea; et al.
Abstract : Background: Echocardiographic screening can detect asymptomatic cases of rheumatic heart disease (RHD), facilitating access to treatment. Barriers to implementation of echocardiographic screening include the requirement for expensive equipment and expert practitioners. We aimed to evaluate the diagnostic accuracy of an abbreviated echocardiographic screening protocol (single parasternal-long-axis view with a sweep of the heart) performed by briefly trained, nonexpert practitioners using handheld ultrasound devices. Methods: Participants aged 5 to 20 years in Timor-Leste and the Northern Territory of Australia had 2 echocardiograms: one performed by an expert echocardiographer using a GE Vivid I or Vivid Q portable ultrasound device (reference test), and one performed by a nonexpert practitioner using a GE Vscan handheld ultrasound device (index test). The accuracy of the index test, compared with the reference test, for identifying cases with definite or borderline RHD was determined. Results: There were 3111 enrolled participants; 2573 had both an index test and reference test. Median age was 12 years (interquartile range, 10–15); 58.2% were female. Proportion with definite or borderline RHD was 5.52% (95% CI, 4.70–6.47); proportion with definite RHD was 3.23% (95% CI, 2.61–3.98). Compared with the reference test, sensitivity of the index test for definite or borderline RHD was 70.4% (95% CI, 62.2–77.8), specificity was 78.1% (95% CI, 76.4–79.8). Conclusions: Nonexpert practitioners can be trained to perform single parasternal-long-axis view with a sweep of the heart echocardiography. However, the specificity and sensitivity are inadequate for echocardiographic screening. Improved training for nonexpert practitioners should be investigated. Abstract : Supplemental Digital Content is available in the text.